The undisclosed history of the Dutch governmental telex-message security 1945-1960 - Oberman, M. R. (Cryptologia, 2024)
The information behind the Dutch governmental telex message security 1945-1960 was stored in private hidden archives, our national General Intelligence and Security Service and the National Archive. Therefore, it became unknow information. The article describes the reasons behind the need for a national developed secure cryptosystem. But also, the obstacles and politics behind the developing and the producing of the OTP-systems at the national PTT for the Ministry of Foreign affairs and the Royal Dutch Navy. It also reveals the politics to transfer the subject cryptography to the national IT industry: Philips, which became the start of the commercial crypto industry in the Netherlands in 1957.